Analisis pedagang di pasar TAC Kota Jambi - Zakia, Zakia Pelita; Zulfanetti , Zulfanetti; Umiyati, Etik (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to: 1) analyze the social and economic characteristics of traders in TAC Market Jambi City. 2).To analyze the significant difference between the income of traders before the Covid-19 pandemic and during the Covid-19 pandemic, and 3).To analyze the factors that determine the income of traders at TAC Market in Jambi City. The method of data collection is the survey method with a questionnaire tool. Then the analytical tools used are Mann Whitney Test and Multiple Linear Regression. Based on the average age of business traders is 39 years, then the average working hours of traders are 9 hours, then there are very many traders selling close to home. Vegetable traders dominate the number of traders. Furthermore, the capital issued by traders for one month is an average of 4,225,000, and the income issued by traders for one month is an average of 3,470,000. There is a difference in the income of traders before the covid-19 pandemic and during the covid-19 pandemic. Based on the regression results, it can be concluded that working capital, business location, and age significantly affect the income of traders at TAC Market in Jambi City. In comparison, working hours and types of the merchandise substantially affect the income of traders at TAC Market, Jambi City.